5th International Conference on Higher Education Advances (HEAd'19) 2019
DOI: 10.4995/head19.2019.8928
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study of early career teachers as culturally responsive teachers

Abstract: The purpose of this study was to advance understanding on how early career teachers imagined themselves to be culturally responsive and how their beliefs and ideologies about teaching a diverse range of learners were challenged and refined during their early years of teaching. This qualitative, exploratory study was conducted in a large, secondary school in eastern Australia that has a highly diverse population of students. Findings indicate that, while these early career teachers lacked preparation for workin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Additionally, ECRs play a role in interculturality-related research in the field of education, where they are required to acquire openness, self-awareness, and a commitment to social justice in order to become inclusive educators (Tangen et al, 2019). The wide range of interculturality-related studies is demonstrated by the acknowledged importance of intercultural sensitivity in many situations, such as multinational organizations and language acquisition (Jedynak, 2021;Ma & Li, 2023).…”
Section: Rationale Behind the Studymentioning
confidence: 99%
“…Additionally, ECRs play a role in interculturality-related research in the field of education, where they are required to acquire openness, self-awareness, and a commitment to social justice in order to become inclusive educators (Tangen et al, 2019). The wide range of interculturality-related studies is demonstrated by the acknowledged importance of intercultural sensitivity in many situations, such as multinational organizations and language acquisition (Jedynak, 2021;Ma & Li, 2023).…”
Section: Rationale Behind the Studymentioning
confidence: 99%
“…Additionally, ECRs play a role in interculturality-related research in the field of education, where they are required to acquire openness, self-awareness, and a commitment to social justice in order to become inclusive educators (Tangen et al, 2019). The wide range of interculturality-related studies is demonstrated by the acknowledged importance of intercultural sensitivity in many situations, such as multinational organizations and language acquisition (Jedynak, 2021;Ma & Li, 2023).…”
Section: Rationale Behind the Studymentioning
confidence: 99%
“…Additionally, ECRs play a role in interculturality-related research in the field of education, where they are required to acquire openness, self-awareness, and a commitment to social justice in order to become inclusive educators (Tangen et al, 2019). The wide range of interculturality-related studies is demonstrated by the acknowledged importance of intercultural sensitivity in many situations, such as multinational organizations and language acquisition (Jedynak, 2021;Ma & Li, 2023).…”
Section: Rationale Behind the Studymentioning
confidence: 99%